Resources development and actors coordination: what role for innovative milieus? - Kebir, Leila; Crevoisier, Olivier (My University, 2007)
The innovative milieu approach consists of exploring how and to which extent local environments contribute to the coherence and the competitiveness of production systems. In line with this work, the present paper explores the articulation of high value added services creation, regional development, and natural and cultural resources evolution. Based on conceptual and empirical research, the central issue of the paper is the link between the resources (understood here as relation processes between objects and production systems), the production systems and the markets in terms of co-ordination in time and space. In this research, innovation dynamics and the innovative milieu appear as key elements in the creation and the maintaining of material resources (landscape, soil, etc.) as well as non-material resources (know-how, knowledge, cultural resources, etc.). The paper argues that innovative milieus play an important role in the identification and the implementation of new resources based on existing objects.
Keywords: cultural resources; natural resources; innovative milieus; coordination; regional development